Strengthening and retrofitting precast concrete buildings to mitigate progressive collapse using externally bonded GFRP strips - Qian, Kai (2020)
Compared to cast-in-situ RC buildings, precast concrete (PC) buildings may have lower redundancy and integrity depending on their construction methods and the types of beam-to-column connection. In this study, a series of multipanel PC beam-column-slab substructures were tested to evaluate the performance of a typical existing PC building with bolted connection, which is a typical dry connection in industrial buildings, subjected to the loss of a single penultimate column scenario. It was found that an existing PC substructure with bolted connections exhibited very low ductility and load-resisting capacity. The deficient connection between the PC slab and beams led to the specimen failing in a brittle manner and gaining fewer benefits from tensile membrane action. To overcome the poor performance of existing PC buildings with bolted connections, improvement in detailing and strengthening schemes relied on glass fiber–reinforced polymer (GFRP) strips were proposed. Based on the test results, the improvement could enhance the redundancy of PC substructures effectively. Moreover, the proposed strengthening scheme further enhances the flexural capacity, initial stiffness, and the postpeak behavior in large deformation stage significantly.